2022
DOI: 10.46827/ejes.v9i4.4290
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Impact of Teacher Factors on Mathematics Performance of Learners With Dyscalculia in Public Primary Schools in Starehe Sub-County, Nairobi City County, Kenya

Abstract: The purpose of this study was to examine the impact of teacher factors on the Mathematics performance of learners with dyscalculia in public primary schools in Starehe Sub-county, Nairobi City County. The study was guided by the social development theory of learning by Vygotsky (1978). The study was a mixed-method research applying a descriptive survey design. The target population was class seven pupils and their Mathematics teachers in 4 public primary schools in Starehe Sub-county. A sample size of 42 class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…When teachers find it difficult to read written presentation, it will be difficult to understand written materials that will attract necessary scores. This is in line with the findings of Uche (2014) who found a high correlation between handwriting quality and scores in a mathematics; and Santangelo and Graham, as cited in Mulanya, (2020) who noted that dysgraphia impacts on the overall academic performance of an individual learner, through both quality and quantity of persuasive and cognitive writing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When teachers find it difficult to read written presentation, it will be difficult to understand written materials that will attract necessary scores. This is in line with the findings of Uche (2014) who found a high correlation between handwriting quality and scores in a mathematics; and Santangelo and Graham, as cited in Mulanya, (2020) who noted that dysgraphia impacts on the overall academic performance of an individual learner, through both quality and quantity of persuasive and cognitive writing.…”
Section: Discussionsupporting
confidence: 90%
“…Most people, the child with dysgraphia inclusive, experience stigma at one point or the other or in one setting or another (Izuchi & Agamugoro, 2021). Finally, it impacts on the overall academic performance of an individual learner, through both quality and quantity of persuasive and cognitive writing (Santangelo & Graham, 2016 as cited in Mulanya, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the study conducted by Macharia et al, 2019, teachers should be trained in using music as an instructional strategy, and it recommended that in the curriculum development, prepared modules provide step-bystep guidelines on how teachers should integrate music during math lessons.…”
Section: Music As Instructional Strategymentioning
confidence: 99%
“…Thus, the need for creating evaluation tools to be used by tutors in learning institutions. Kahenya (2021) conducted a study based on the effect of tutor factors on the arithmetic achievement of scholars with dyscalculia in primary public institutions in the Starehe sub-county, Nairobi. This study found out that most of the mathematics tutors in the sub-county have a lot of tutoring knowledge, but only a few had gained formal instruction in special education.…”
Section: Research Studies On Dyscalculia In Kenyamentioning
confidence: 99%